2020
DOI: 10.34119/bjhrv3n5-112
|View full text |Cite
|
Sign up to set email alerts
|

Filhos autistas e os fatores de insegurança da mãe quanto ao seu futuro / Autistic children and the factors of insecurity of the mother regarding their future

Abstract: Filhos autistas e os fatores de insegurança da mãe quanto ao seu futuro Autistic children and the factors of insecurity of the mother regarding their future

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Given the results found, the responsibility of the caregiver has been presented as an exhausting task, resulting in increased levels of anxiety and reduced quality of life for the caregiver, who is usually the mother of the child with autism spectrum disorder (ASD). The mother, as the child's caregiver, is responsible for seeking treatment, for the daily care of her child, and as such, needs to make adaptations in her daily life that can result in the impoverishment of her social, emotional and professional life, and consequent physical and of this woman [14]. These data corroborate those of studies carried out by Anjos et al [15] and Tavares et al [14] who demonstrated the prevalence of mother caregivers in their research.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Given the results found, the responsibility of the caregiver has been presented as an exhausting task, resulting in increased levels of anxiety and reduced quality of life for the caregiver, who is usually the mother of the child with autism spectrum disorder (ASD). The mother, as the child's caregiver, is responsible for seeking treatment, for the daily care of her child, and as such, needs to make adaptations in her daily life that can result in the impoverishment of her social, emotional and professional life, and consequent physical and of this woman [14]. These data corroborate those of studies carried out by Anjos et al [15] and Tavares et al [14] who demonstrated the prevalence of mother caregivers in their research.…”
Section: Discussionsupporting
confidence: 81%
“…The mother, as the child's caregiver, is responsible for seeking treatment, for the daily care of her child, and as such, needs to make adaptations in her daily life that can result in the impoverishment of her social, emotional and professional life, and consequent physical and of this woman [14]. These data corroborate those of studies carried out by Anjos et al [15] and Tavares et al [14] who demonstrated the prevalence of mother caregivers in their research. However, studies by Alshekaili [16] and Alshahrani and Algashmari [17] found a prevalence of male caregivers.…”
Section: Discussionsupporting
confidence: 81%
“…The mother, as the child's caregiver, is responsible for seeking treatment and for the daily care of her child, and as such, needs to make adaptations in her daily life that can result in the impoverishment of her social, emotional, and professional life, as well as consequent physical detriment [18]. In this context, the responsibility of the caregiver has been presented as an exhausting task, resulting in increased levels of anxiety and reduced quality of life for the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…The mother, as the child's caregiver, is responsible for seeking treatment, for the daily care of her child, and as such, needs to make adaptations in her daily life that can result in the impoverishment of her social, emotional and professional life, and consequent physical and of this woman [16]. In this context, the responsibility of the caregiver has been presented as an exhausting task, resulting in increased levels of anxiety and reduced quality of life for the caregiver.…”
Section: Discussionmentioning
confidence: 99%